Nilai-Nilai Pancasila dalam Kegiatan Ekstrakurikuler Pramuka di SMP Negeri 4 Waru Sidoarjo - Ardhana, Nehru Firdaus; Srinarwati, Dwi Retnani; Suyono, Suyono (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
Education plays an important role in shaping the character of students and instilling the noble values of the nation. Pancasila as the basis of the state needs to be internalised through various educational activities, including extracurricular activities, such as: Scouts. This study aims to analyse the values of Pancasila which are reflected in the extracurricular activities of Scouts of grade VIII students at SMP Negeri 4 Waru Sidoarjo. The research uses a qualitative approach with data collection techniques through observation, interviews, and document review. Data analysis is carried out through data reduction, data presentation, and conclusions drawn, with validity tests through triangulation of sources and techniques. The results of the study show that the five values of Pancasila are internalised through behavioural habituation, value-laden assignments, and joint reflection. Supporting factors include consistent school policies, commitment of Scout coaches, design of activities based on group work, and support for adequate educational facilities. Scout extracurricular activities are an effective medium in instilling and internalising Pancasila values for grade VIII students of SMP Negeri 4 Waru, so as to contribute significantly to the formation of students' character that reflects the identity of the Indonesia. The findings are focused on a single informal educational setting within a specific location, meaning the results primarily describe the dynamics of life-space and vulnerability within that unique context.